Photoluminescence of epoxy resin: explanation of the increase in the flux of photoluminescent radiation during the initial stage of the curing process - Michaela Mikuličová; Milan Navrátil; Vojtěch Křesálek (Materials Research Express, 2025)
When using luminescence spectroscopy to study the curing of epoxy resins, there is an increase in the luminescent radiant flux at the beginning of the curing process. The paper clarifies this phenomenon, which limits the determination of the fundamental kinetic constants of the chemical crosslinking reaction. The reflectance measurement shows that the mentioned phenomenon is of physical origin and is caused by a change in the refractive index of the mixture after the addition of the hardener. This change in refractive index is significant in the context of luminescence spectroscopy as it affects the observed luminescent radiant flux. There is a decrease in the refractive index and, therefore, a decrease in reflectance at the material-atmosphere interface, which causes an increase in the number of photons that leave the material. This assumption was further confirmed by measuring the refractive index for the given wavelengths and by the calculation. The paper provides a method of estimating the time constant of the physical process of increase in the flux of photoluminescent radiation. Therefore, it is possible to determine when this process ends, which is crucial for the subsequent estimation of the kinetic parameters of the chemical curing.